The Effects Of Study-Summary-Quiz Based Flipped Learning Model On Pre-Service Teachers’ Ict Skills, Achievement, Engagement, And Self-Efficacy - Samaila, Kamaludeen (2022)
Traditional lecture-based method for teaching ICT in Education course in Nigerian higher education institutions contributes to the pre-service teachers’ poor academic achievement, inadequate practical skills, depleted engagement, and limited self-efficacy. As an ICT course with unique characteristics, it requires student-centred and technology-based learning approaches. The flipped learning model is one of the technology-based learning approaches used commonly in learning institutions where pre-class and in-class learning activities have a significant role.